Pemerolehan dan Pembelajaran Bahasa Kedua Pemandu Wisata Lokal di Desa Bongkasa Pertiwi: Hipotesis Krashen - Anak Agung Istri Manik Warmadewi; I Made Astu Mahayana (LINGUA : Jurnal Bahasa, Sastra, dan Pengajarannya, 2021)
Tourism development has had a tremendous influence on the life of Balinese people. Apart from a large number of tourist destinations opened, human resources also need to be considered in order to provide good service for the tourist who visits Bali. The main thing is how to communicate in English fluently. Mastered English as a second language can not be separated from the theory of language acquisition. Mastered in a second language can be as an acquiring, on the other hand, it can be as learning. The aim of this research is to explain how the local guide in Bongkasa Pertiwi Village mastered English as a second language. The data were collected through interviewing, distributing questionnaires to the local guide or the other tourist actors who lived in that village. A mixed method (quantitative and qualitative) was used for solving the problem. By using the Krashen hypothesis, the results obtained are some informants mastered English as a second language naturally and the other informants mastered English by learning.